Monophasic action potentials and electrocardiographic manifestations observed in injured or damaged heart muscle - Experimental work - Alzamora Castro, V. (1958)
By various methods has been possible to obtain all of monophasic action potential in accordance with the theory of the membrane were theoretically predictable. In an injured area resting potential of the membrane may remain unchanged, being zero or supernormal subnormal. Consequently they can register monophasic action potential currents without damage, or injury caused by streams or hipopolarización membrane hyperpolarization. The only essential requirement to record monophasic action potentials is blocking the excitation, the current of injury is a phenomenon that attachment may or may not be present. When the heart muscle is severely injured the excitation process is blocked and then monophasic action potentials are inscribed. By decreasing the damage processes depolarization and repolarization are performed slowly and then enroll QRS-T complex and large widths. When the deterioration is less excitation process is done faster. Experiments suggest the existence of a correlation between the degree of market harm or damage and the degree of blocking cardiac excitation fiber. The sequence of changes in the electrocardiogram in cases in which there was uniform damage, severe but reversible, can explain the genesis of abnormal curves recorded at exploring unevenly worn or damaged muscle areas. In this form the meaning of abnormal electrocardiogram that is recorded in daily clinical practice in different circumstances is required.